EFEKTIVITAS IMUNOSTIMULAN DARI EKSTRAK DAUN BANGUN-BANGUN (Coleus amboinicus L.) PADA TIKUS JANTAN DENGAN STIMUNO SEBAGAI PEMBANDING TAHUN 2021 - Anggun Syafitri; Linta Meliala (Jurnal Penelitian Farmasi & Herbal, 2021)
Background: This modern society does not know much about the benefits of medicinal plants for health, because people are more familiar with drugs from chemicals. Many plants have imunostimulant activities, one of them is bagun-bangun (Coleus amboinicus L.) which is widely used as a stimulant, carminative, antispasmodic, diuretic, antioxidant and anti-rheumatic.The purpos of thiss research wass to determin the effective of etanol extract of bagun-bangun seeds (EEDB) on imunostimuensitivity lan hypereduction in male white rats compared with stimuno. Methods: The method used experimental. The sample of in this research was bangun-bangun seeds which were take purposivelyy without comparring samples from the other regiions, thenit is extracted by maceration using 80% ethanol and made in the form of thick extract. The results of the study: Imunostimulan efectivity effects were tested on 25 male rats with 5 treatment groups namely, negative group (CMC Na 1%), positive group (stimuno), EEDB group 100mg/kgBW, EEDB group 200mg/kgBW, and EEDB group 300mg/kgBB. Data analysis use the one way ANOVA method.The resultss of the studyy show thatt the most effectiv treatmentt was simvastatin and among the efective dosage ofEECS was a dose of 300mg/KgBW. The resultss of data analysis from the tthree EEDB groups had an effect on cholesterol reducttion due to the sig value <0.05. Based on anovva one way analysis of the five most effective treatmentss was stimuno then EEDB 300mg/kgBW, EEDB 200mg/kgBW, EEDB 100mg/kgBW and CMC Na 1%.EEDB has an effect on imunostimulan reduction but does not give better results than stimuno.